Ensino de física das radiações ionizantes: do senso comum ao conhecimento científico - Pinheiro, Di Angelo Matos (2016)
We lived with the radiation from various sources, both natural and artificial, and indeed life on Earth exists only because of it being a key aspect of our daily lives. Although most students have heard about radiation, a significant number do not know the subject, basic items such as their benefits, and the difference between ionizing and non-ionizing radiation. The vision of the student is the one generated by the media, stating that the radiation is harmful. Thus, this study aims to address the topic in the classroom, through a didactic sequence for students of vocational education in meaningful learning theory perspective of David Ausubel, so that takes the student out of the mediatic idea, common sense, and formulate scientific concepts. The work begins with a brief study of the meaningful learning and its key employees subsequently approach the teaching of physics of radiation - ionizing radiation immediately will relate the physics of radiation with the meaningful learning of Ausubel. Finally we present the teaching sequence presented to students of the Federal Institute of Amazonas - IFAM / Manaus Campus Center, and present the results.